Factors affecting bankruptcy : the case of Malaysia / Hilwa Hilmy, Shaliza A. Mohd Z and Norasyikin A. Fahami - Hilmy, Hilwa; Mohd Z., Shaliza A.; A. Fahami, Norasyikin (Faculty of Business Management, 2013)
This paper intends to determine the factors affecting bankruptcy cases in Malaysia. The data ranges from 1999 to 2012 on a yearly basis consist of the independent variables such as non-performing loans, unemployment, per capita income and bankruptcy cases as dependent variable. The result shows that non-performing loan and unemployment has statistical significant relationship towards bankruptcy case in Malaysia. However, per capita income has no statistical relationship towards bankruptcy case in Malaysia. The results suggest that Malaysians fails to repay loan due to inability to settle their debt and also loss of work or being unemployed. This research is done in the context of Malaysia as single entity instead of a pool of countries or states/counties and the variables are all statistically analyzed. Also, the current research gives perspective and insight from academic point of view to assist government in their decision making as far as bankruptcy is concern.